Contextualizing Mahmud Yunus’ Islamic Education Concept in Madrasah Aliyah - Hilda Ainissyifa; Abdul Kosim Nurseha (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
Islamic education will always develop in every era to respond to the world’s changes. This situation can be a challenge for Islamic education to ensure its advancement in terms of its existence and management. This study aims to investigate the implementation of the Mahmud Yunus concept of Islamic education at Madrasah Aliyah Miftahul Huda Tegalwaru. The method used in this study is a descriptive method with a qualitative approach. Data were collected using observation, interview and documentation. The Analysis of data is done through: data reduction, data interpretation, and conclusion. The results of this study indicate that the concept of Mahmud Yunus’ Islamic education can be implemented to overcome the problems of Islamic education. At Madrasah Aliyah Miftahul Huda Tegalwaru, the concept is implemented starting from the goals of Islamic education which are based on moral education, an integrated curriculum, methods that always evolves, educators who must be willing to learn with technological advances, and evaluations that use letters rather than numbers.